Biogeography of Azorean plant invaders - Silva, Luís (2010)
Alien plants are a major component of the Azorean vascular flora. We present a general biogeographic analysis of the taxa considered as introduced in the Archipelago. This work results from the construction of a data-base of Azorean plant invaders. Of the 996 taxa recorded for the Azores, 6,6% are considered endemic, 10,2% native, 72.6% alien, and 10,5% to be of uncertain status. The percentage of alien taxa is lowest in the Pteridophyta (26,0%) and highest in the Dicotyledoneae (78,9%). Significant differences were found between islands for the proportion of invaders. The highest percentages were found in São Miguel, Terceira and Faial, and the lowest in Flores and Corvo. A quadratic model fitted a regression between percentage of invaders and human population density, and might reflect the existence of a higher propagule pressure in some of the islands. Many of the invaders are also found in mainland Portugal and in other Macaronesian islands. The invaders are largely Palearctic in origin or Sub-cosmopolitan, with a wide geographic distribution, and have also been introduced in other regions of the world.